Parâmetros de resistência do solo para dimensionamento de sistemas de drenagem em estradas não pavimentadas - OLIVEIRA, João Fonseca de (2008)
This work was developed mainly aiming the determination of the erodibility and the critical shear stress in non-paved roads, focusing on the reduction of the eminent risks of occurring erosion in these roads, based upon a drainage system dimensioning using local resistance values. In order to achieve these values a yield simulator was built, which model consists of an improved version of the equipment proposed by Griebeler (2005), utilized in superficial yield testing directly at the drainage channel of the road and in collecting the eroded material. The simulator was installed in soils of roads of Goiânia (E1), Baliza (E2), Doverlândia (E3) and Morrinhos (E4, E5 e E6) , all of which are in the state of Goiás. The tests were performed with three repetitions for each passage of the vicinal roads. For each test were utilized five channels with different crescent volumetric flow rates, in a way to simulate the ascending curve of a yielding hydrogram, where each channel was collected in a proper recipient, for later determination of the amount of eroded material (debris). Samples were also collected from non-deformed soil, utilizing an Uhland sampler, aiming to determine the density of the soil. Furthermore, the declivity of the road and samples for characterizing the granulometric curves and determining the Atterberg limits were also measured and collected. The results found showed erodibility (g.cm-2.min- 1.Pa-1) and critical shear stress values respectively of 0.0036 and 2.00 for E1; 0.0099 and 2.06 for E2; 0.0582 and 3.93 for E3; 0.0073 and 3.78 for E4; 0.0075 and 4.87 for E5; and, 0.0054 and 3.74 for E6. These values appear highly elevated for the condition of roads, indicating high erosion risk, a fact that can be observed from the conservation state in which they can be found. The soils of the roads were classified as Sandy loam (E1), Sandy (E2), Clay loam (E3), Sandy clay (E4), Sandy loam (E5) and Sandy clay loam (E6). The classification of the soils of the roads, with little clay material, which works as a cementer, helps explain the elevated values obtained for the erodibility and critical shear stress. The soil density values (g.cm-3) observed were, respectively for roads E1 to E6, 1.58; 1.64; 1.53; 1.41; 1.63 and 1.60. Through the simulation performed using the Roads Griebeler (2005) software and utilizing the values observed in the field, the fact that road E1 obtained the greatest space management, mainly due to its lower erodibility. However, for the remaining roads, the software pointed out the need to build drains nearby, further indicating the need to make alterations in their drainage channels as well as their consisting material, so that their erodibility would be reduced. The composition of the material can be made through the mixture of a greater quantity of cementing material, such as clayey soil, to the material of the road, enhancing the soil s resistance to the erosive process. The model has proven to be highly sensitive to the alterations in the erodibility of the soil and in the declivity of the road.